Teacher Strategy in Learning Mathematics in Class B at TK Aisyiyah Bustanul Athfal 06 Medan in Academic Year 2023/2024 - Sari, Rili Fitria; Sariana Marbun (MultiTech Publisher, 2023)
This research aims to find out the math learning strategies of TK Aisyiyah Bustanul Athfal 06 Medan Class B teachers. The results showed that there were many variations of mathematics learning strategies used by teachers in Teratai class, including direct learning strategies, indirect learning strategies, interactive learning strategies, and autonomous learning strategies, but when used in Teratai class teachers were more likely to use indirect learning strategies, while the use of direct learning strategies, interactive learning strategies, and autonomous learning strategies was still not optimal. So in Mawar class, the strategies used by teachers in teaching mathematics are still relatively single, the strategies used include direct learning strategies, indirect learning strategies, and indirect learning strategies. Among these strategies, Mawar class teachers more often use direct learning strategies. Meanwhile, the use of indirect learning strategies and autonomous learning strategies is still less than optimal.